Potential economic values of low-vapor-pressure gasoline-range bio-blendstocks: Property estimation and blending optimization. (1st August 2021) - Jiang, Yuan; Phillips, Steven D.; Singh, Avantika; Jones, Susanne B.; Gaspar, Daniel J.
Highlights: Developed methodology to link properties with economic values of bio-blendstocks. Developed data-driven non-linear blending model for gasoline-range blendstocks. Evaluated the potential economic values of six gasoline-range bio-blendstocks to refiner. Identified RON has the highest impact on the value of bio-blendstocks, while other properties are also important when the final fuel is constrained by a given property. Abstract: Adding bio-blendstock into gasoline can reduce greenhouse gas emissions and potentially enhance fuel properties and boost engine efficiencies. A competitive bio-blendstock should have lower prices and/or superior properties. Gasoline is specified by final blended properties rather than compositions, while adding bio-blendstocks, most likely oxygenates, will modify the property mixing rules due to the non-ideal interactions between polar and nonpolar components. This paper presents an equation-of-state model for predicting Reid vapor pressure, non-linear blending models for computing key properties of final products, and an optimization approach to identify key economic drivers. Those models are used to estimate the potential economic value of bio-blendstocks, which is presented by its calculated break-even value as a feedstock to petroleum refineries for gasoline blending without any government subsidy or renewable tax credit. In additional to ethanol, six low-vapor-pressure bio-blendstock candidates were evaluated: i-propanol, n-propanol, i-butanol, diisobutylene, cyclopentanone, and a mixture of furans. Reid vapor pressure, distillation temperatures, and octane numbers were identified as the key economic drivers of adding bio-blendstock to a petroleum-derived base fuel. The calculated economic value ranks as furan mixture (4.9) > cyclopentanone > n -propanol ≈ iso -propanol > iso -butanol > diisobutylene (2.4) in US dollar per gasoline gallon equivalent (/gge) in 2013 to 2017 5-year averaged price basis. The bio-blendstocks with higher octane numbers may have higher potential economic values. The uncertainties in property predictions may lead to roughly 15% deviation in the potential economic value.